The Toxicity of Beauty Standards: Body Image Perception Among Women Acne Fighters - Aqilah, Najwa Salma; Trihandayani, Dewi (Kuras Institute, 2024)
Beauty is often closely linked with physical appearance in the current digital era. Prevailing beauty standards in society presuppose certain criteria for beauty, making adherence to these standards the primary basis for assessing one's body image. This study aims to provide an overview of the body image perceptions among women who struggle with acne or